The Challenge of Admitting Electronic Evidence in Civil Procedure Law - Adinda, Fadhel Arjuna; Rahmawati, Ema; Suparman, Eman; Arifin, Ridwan; Ezzerouali, Souad (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
In the digital age, the use of electronic evidence in civil disputes has become increasingly common. However, judges often face significant challenges in accepting and evaluating electronic evidence due to concerns about its authenticity, integrity, and relevance. This paper examines the factors contributing to judicial doubts regarding electronic evidence in Indonesian civil litigation and explores the implications of such doubts on the resolution of legal disputes. Drawing on case law, legal theory, and practical challenges, the paper identifies key issues such as the ease of manipulation, lack of standardized procedures for collecting and preserving digital evidence, and the limited understanding of technology among many judges. These factors create a significant barrier to the effective use of electronic evidence in court, leading to delays, case dismissals, or unjust outcomes. The paper also discusses potential solutions to overcome these challenges, including the need for clearer legal frameworks, the role of forensic digital experts, and judicial education in information technology. By addressing these concerns, this paper aims to highlight the critical importance of building trust in electronic evidence, ensuring its proper use in civil dispute resolution, and promoting a more efficient and fair legal process. Ultimately, the study proposes strategies to strengthen the role of electronic evidence in Indonesian civil law while maintaining judicial integrity and ensuring the protection of all parties involved.